A non-syndromic orofacial cleft risk locus links tRNA splicing defects to neural crest cell pathologies - Bartusel, Michaela; Kim, Skylar X.; Rehimi, Rizwan; Darnell, Alicia M.; Nikolić, Miloš; Heggemann, Julia; Kolovos, Petros; van Ijcken, Wilfred F. J.; Varineau, Jade; Crispatzu, Giuliano; Mangold, Elisabeth; Brugmann, Samantha A.; et al. (The American journal of human genetics, 2025)
Orofacial clefts are the most common form of congenital craniofacial malformation worldwide. The etiology of these birth defects is multifactorial, involving genetic and environmental factors. However, in most cases, the underlying causes remain unexplained, precluding a molecular understanding of disease mechanisms. Here, we integrated genome-wide association data, targeted resequencing of case and control cohorts, tissue- and cell-type-specific epigenomic profiling, and genome architecture analyses to molecularly dissect a genomic locus associated with an increased risk of non-syndromic orofacial cleft. We found that common and rare risk variants associated with orofacial cleft intersect with an enhancer (e2p24.2) that is active in human embryonic craniofacial tissue. We mapped e2p24.2 long-range interactions to a topologically associated domain harboring MYCN, DDX1, and CYRIA. We found that MYCN and DDX1, but not CYRIA, are required during craniofacial development in chicken embryos. We investigated the role of DDX1, a key component of the tRNA splicing complex, in cranial neural crest cells (cNCCs). The loss of DDX1 in cNCCs resulted in the accumulation of unspliced tRNA fragments, depletion of mature intron-containing tRNAs, and ribosome stalling at codons decoded by these tRNAs. This was accompanied by defects in both global protein synthesis and cNCC migration. We further showed that the induction of tRNA fragments is sufficient to disrupt craniofacial development. Together, these results uncovered a molecular mechanism in which impaired tRNA splicing affects cNCCs and craniofacial development and positioned MYCN, DDX1, and tRNA processing defects as risk factors in the pathogenesis of orofacial clefts.
Gesehen am 20.10.2025